Propranolol degradation through processes based on the generation of hydroxyl free radical. (30th December 2021) - Nájera-Aguilar, Hugo Alejandro; Mayorga-Santis, Rosario; Gutiérrez-Hernández, Rubén Fernando; Santiesteban-Hernández, Antonio; Rodríguez-Valadez, Francisco J.; Ulloa-Gutiérrez, Diego Alberto; Araiza-Aguilar, Juan Antonio; Cruz-Salomón, Abumalé
Abstract: Pharmaceutical substances such as propranolol (PRO) are an emerging class of aquatic contaminants that have increasingly been detected in ground and surface water. For this reason, the aim of this study was to evaluate the efficiency of advanced oxidation systems for the PRO degradation. The tests started with anodic oxidation (AO), using 0.01, 0.05, and 0.1 M Na2 SO4 as the supporting electrolyte and 16, 32, 48, and 64 mA cm −2 as current density. Under the best conditions obtained in AO, the electro-Fenton (EF) process was reviewed, where the effect of Fe 2+ was analyzed with 5, 10, 15, and 20 mg Fe 2+ L −1 . The Fenton reaction (FR) was studied using the Fe 2+ concentration that promoted the highest percentage of PRO removal and initial concentration of 16 mg L −1 of H2 O2, in addition to these conditions, in the photo-Fenton (PF) system, the effect of UV light with wavelengths 254 and 365 nm were evaluated. The results obtained showed that the degradation efficiency of the EF > AO > PF > FR system along with a percent removal of 94.52, 90.4, 25.97, and 4.4%, respectively. The results showed that PRO can be removed through the studied systems, with the EF system being the most efficient. HIGHLIGHTS: Propranolol degradation was evaluated through various advanced oxidation processes. The advanced oxidation process with the highest degradation efficiency of propranolol was determined. Under the evaluated conditions, the electro-Fenton (EF) system was the best advanced oxidation process for propranolol degradation. Graphical Abstract